PENGARUH KUALITAS PRODUK, FITUR PRODUK DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN TAS SOPHIE MARTIN PADA BUSINESS CENTRE UMI SUTINDARWATI GRESIK (Fakultas Ekonomi Universitas Gresik, 2017)
This study aims to determine the effect of product quality, product features and product design to the purchase decision of sophie martin bag at bussiness center (bc) Umi Sutindarwati Gresik. The research approach used in this research is quantitative approach. The number of samples researched were 56 respondents. The independent variables in this study are Product Quality (X1), Product Feature (X2), Product Design (X3), while the dependent variable is Purchase Decision (Y). The results showed that product quality (X1) partially and simultaneously significantly influence purchasing decisions, product features (X2) partially and simultaneously have a significant effect. Product design (X3) is partially influential but simultaneously has no significant effect. Suggestions from this research can be developed by adding the variables in the study and the samples taken can be expanded its territory.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477685